Uji Antagonis Jamur Rizosfer Isolat Lokal terhadap Phytophthora sp. yang Diisolasi dari Batang Langsat (Lansium domesticum Corr.) - Mukarlina, Fety, Siti Khotimah, (Jurnal Protobiont, 2015)
Stem canker caused by the Phytophthora sp. fungus is one of the diseases in langsat (Lansium domesticum).The disease can be controlled using biological agents in the form a rhizosphere fungus which is antagonistic against pathogenic fungi. This research aims to identify the types of fungi from the rhizosphere of langsat and determine the ability of these fungi in slowing down the growth of Phytophthora sp. The isolation of Phytophthora sp. fungus was done by the direct planting method, while the isolation of the rhizosphere fungi by the dilution method and the antagonistic test was performed with a paired method. The antagonistic fungi successfully isolated were Mucor sp.1 F1, Mucor sp.2 F2, Penicillium sp.1 F3, Penicillium sp.2 F4,Penicillium sp.3 F5, Penicillium sp.4 F6, Trichoderma harzianum F7 dan T. viride F8. Based on the research results, there of the growth of Phytophthora sp. was inhibited by the T. harzianum F7 with highest antagonistic percentage 68,93%.